Factors Associated with Drug Consumption Without Scientific Evidence in Patients with Mild COVID-19 in Peru - Soriano-Moreno, David R. (2022)
Objective This study aimed to evaluate the factors associated with the consumption of drugs without scientific evidence in patients with mild COVID-19 infection in Peru. Methods An analytical cross-sectional study was carried out including 372 adult patients with a history of mild COVID-19 disease. Factors associated with drug consumption were evaluated by Poisson regressions with robust variance adjustment using the bootstrapping resampling method. Results Seventy-two percent consumed some medication without scientific evidence, with antibiotics (71%) and ivermectin for human use (68%) being the most commonly used. Factors associated with the consumption of drugs to treat mild COVID-19 infection were thinking that the drugs are not effective (adjusted prevalence ratio, 0.55; 95% confidence interval, 0.41-0.74) and not being informed about the efficacy of the drugs (adjusted prevalence ratio, 0.48; 95% confidence interval, 0.36-0.65). Conclusions Education of the population seems to be the main factor that increases the consumption of drugs without scientific evidence in the Peruvian population to treat mild COVID-19.